The Crown and the Turban: Muslim and West African Pluralism by Lamin Sanneh. Boulder, Colorado, and Oxford: Westview Press, 1997, xiii+ 290 pp. (American Journal of Islam and Society, 1998)
The Crown and the Turban is a new, valuable, and controversial contributionto two debates. First, it is a part of the debate on Africa's triple heritage: Africantradition, Islam, and Christianity. Second, it contributes to the debate on "secular"versus "religious" governance.For the first debate, the author argues that Muslims in West Africa are part oftwo encounters. First, they encounter the indigenous people and societies andparticularly their traditional religions and political institutions. Second, theyencounter Europeans who colonized and still indirectJy dominate West Africa.The reason for tension, the author claims, is what he calls "Islamic politicalism"and Muslim militancy on one hand and African tolerance and European secularismon the other.However, African Muslims are in an advantaged position compared toAfrican Christians. African Muslims are indigenous and Islam is considered anAfrican religion. Moreover, African Muslims demonstrate a political confidence based on an authentic tradition and long experience of Muslim rule in precolonialWest Africa (p. 1).Nevertheless, the author argues that Africa offers a fresh opportunity to theadherents of the two missionary faiths, i.e., Islam and Christianity, vis-his thepluralist challenge of indigenous societies. Muslim and Christian Africans arealready favored relatives in the African household but without the prodigal rightor presumption to dispossess it or each other (p. 181).For the second debate, the author argues that Africa offers the promise, andthe attendant hazards, of formulating and resolving the most crucial of debatesfor religious modernization: the debate on secular versus religious governance(p. 182). In the fmal analysis, the author approves and defends the secular governanceas opposed to the religious one ...